1t' tmd gel for solar-driven water evaporation and voc degradation

CN122974339APending Publication Date: 2026-10-27CITY UNIVERSITY OF HONG KONG
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610414410.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-03-12
Filing Date
2026-03-31
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

具体而言,本发明旨在通过利用经过相工程化的半金属1T'相TMD,来解决传统半导体2H相TMD的固有局限性以及不稳定的1T相问题

Benefits of technology

[0032]本发明有效解决了现有太阳能蒸发技术中长期存在的问题。常规光热材料往往存在太阳能吸收受限或相位降解过快的问题,而1T'-TMD的半金属性确保了其本质稳定性和宽带太阳能反应。由1T'-TMD促进形成的水凝胶互连多孔结构提供了高效的水输送和局部隔热效果,克服了金属基材料中常见的散热过快问题。最重要的是,1T'相的高电子传输能力抑制了电子-空穴复合,解决了通常阻碍2H相TMD光催化剂效率的载流子分离迟缓问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974339A_ABST
    Figure CN122974339A_ABST
Patent Text Reader

Abstract

The present invention relates to an engineered 1T' phase transition metal dichalcogenide (1T'-TMD) gel for integrated solar-driven water evaporation and photocatalytic pollutant degradation. The present invention utilizes semimetallic 1T' phase nanosheets as an intrinsic active photothermal agent with superior broadband solar absorption and prolonged carrier-lattice energy transfer compared to traditional semiconductor 2H phase materials. By incorporating these 1T'-TMD nanosheets into a porous hydrogel matrix, the present invention effectively reduces the water activation enthalpy and enhances interfacial evaporation efficiency. Furthermore, 1T'-TMD is coupled with a semiconductor catalyst (e.g., graphite phase carbon nitride) to facilitate exceptional charge carrier separation and transport, enabling simultaneous photodegradation of volatile organic compounds (VOCs) and other water pollutants. This robust platform exhibits excellent salt tolerance, mechanical durability, and stable freshwater production, providing an expandable and multifunctional solution for next-generation solar desalination and sustainable wastewater management.
Need to check novelty before this filing date? Find Prior Art

Description

Cross-references to related applications

[0001] This application claims priority to U.S. Provisional Patent Application No. 63 / 786,992, filed April 11, 2025, and U.S. Patent Application No. 19 / 564,259, filed March 12, 2026, which are incorporated herein by reference in their entirety. Technical Field

[0002] This invention relates to advanced materials for solar-driven energy applications, and more specifically, to phase-engineered 1T' phase transition metal chalcogenide-based (1T'-TMD) gels and their application in integrated solar-driven water purification and photocatalytic degradation of volatile organic compounds (VOCs). Background Technology

[0003] Interfacial solar-driven seawater evaporation has become an attractive and sustainable solution to the growing global freshwater crisis due to its efficient utilization of abundant solar energy and environmental compatibility. Transition metal chalcogenides (TMDs) have attracted widespread attention in solar thermal applications due to their strong solar absorption, unique electronic structure, high specific surface area, and cost-effectiveness. Because of their inherent layered crystal structure, TMDs can be synthesized into two-dimensional (2D) nanosheets through top-down techniques such as mechanical or chemical exfoliation. Research and development using TMD nanosheets for seawater evaporation typically focuses on external modification, such as heteroatom doping or hybrid composite design, to enhance light absorption and promote water activation. However, despite rapid progress, the development of large-scale and durable solar evaporators remains limited by limited light absorption and high enthalpy of vaporization.

[0004] The crystal phase plays a decisive role in determining the physicochemical properties and photothermal performance of TMDs. Previous studies, such as Young-Shin Jun... 1 He Wang and others 2 Phase transitions from the semiconductor 2H phase to the metallic 1T phase have been explored using lithium intercalation or hydrothermal methods to enhance solar absorption and reduce band gaps. However, these methods typically result in mixed-phase materials (e.g., 1T / 2H MoS2), with reported evaporation rates as low as 1.52 kg m³. -2 h -1 The results remain relatively low. Furthermore, the 1T phase TMD is thermodynamically unstable under environmental conditions and readily transforms back into the 2H phase, significantly limiting its practical durability. (US Patent Application No. 2022 / 0348476A1) 3 Although attempts have been made to utilize other structures (such as the 3R crystal structure), the specific photothermal properties of such materials have not been disclosed, and there is a lack of relevant comparisons.

[0005] Existing technologies also face significant challenges in terms of material composition and synthesis. For example, Chinese Patent No. CN112707391B... 4 The research focuses on composite materials of graphene and molybdenum disulfide, but its main emphasis remains on 2H-phase TMD and carbon-based materials. Although Chinese Patent No. CN115746383A... 5 While molybdenum disulfide (MoS2)-based gels have been proposed, their associated synthesis processes are often quite complex, hindering large-scale applications. Furthermore, current exfoliation methods for producing nanosheets typically rely on hazardous organolithium reagents that require operation in an inert atmosphere, or on electrochemical methods that use expensive intercalating agents and cause nanosheets to aggregate in water.

[0006] Besides desalination, traditional solar-driven evaporation systems are further hampered by the accumulation of volatile organic compounds (VOCs), which can co-evaporate with water vapor and contaminate the collected condensate. Although photocatalysis has been explored as a strategy for intercepting and degrading such VOCs, widely used photocatalysts (e.g., TiO2 and g-C3N4) typically suffer from low charge separation efficiency and limited carrier transport mobility, thus limiting their practical performance. Two-dimensional photocatalysts (TMDs) have attracted increasing attention as cocatalysts due to their ability to promote charge extraction and provide additional active sites. However, most reported TMD-based systems rely on semiconductor 2H phase materials, whose catalytic activity is typically confined to edge sites, and whose inherent carrier mobility remains limited.

[0007] Compared to semiconductor 2H-phase TMD, half-metal 1T'-phase transition metal dichalcogenides are characterized by relatively higher electronic conductivity and more delocalized electronic states, which are beneficial for improving charge transport and reducing electron-hole pair recombination. Therefore, there is still an urgent need in the field for a stable, high-purity half-metal material that can be used as a highly efficient photothermal material for solar-driven evaporation, as a cocatalyst with enhanced electron transport capabilities, and can be prepared by a simple, high-yield, and cost-effective exfoliation process. Summary of the Invention

[0008] The primary objective of this invention is to provide a multifunctional material and system capable of simultaneously achieving efficient solar-driven photothermal water evaporation and photocatalytic degradation of organic pollutants, such as volatile organic compounds (VOCs). Specifically, this invention aims to address the inherent limitations and unstable 1T phase issues of traditional semiconductor 2H phase TMDs by utilizing phase-engineered 1T' phase TMDs. By integrating these unconventional nanosheets into a specifically designed gel matrix, this invention provides a durable, scalable, and economically viable solution for sustainable seawater desalination and wastewater treatment.

[0009] To achieve the above objectives, this invention introduces high-purity 1T'-phase TMD into a hydrogel matrix to form an interconnected porous photothermal system. The technology involves synthesizing high-purity 1T'-phase crystals using a salt-assisted method, followed by obtaining ultrathin nanosheets through a high-yield chemical exfoliation process. These nanosheets are then integrated into the hydrogel with ultra-low loadings, typically between 0.5 wt% and 8 wt%. Furthermore, by coupling 1T'-TMD with semiconductor catalysts such as graphitic carbon nitride (g-C3N4), this invention enables the construction of a photothermal-photocatalytic hybrid system, thereby achieving the interception and degradation of pollutants while generating steam.

[0010] According to a first aspect, the present invention provides a photothermal hydrogel for solar-driven water evaporation and contaminant removal. The hydrogel comprises: a polymer matrix containing an interconnected porous framework; and semi-metallic 1T' phase transition metal chalcogenide (1T'-TMD) nanosheets distributed within and anchored to the interconnected porous framework. Based on the total weight of the hydrogel, the concentration of the 1T'-TMD nanosheets ranges from 0.5 wt% to 8.0 wt%.

[0011] In one embodiment, the 1T'-TMD nanosheet comprises a transition metal M and a chalcogenide element X, represented by the chemical formula MX2, wherein M is selected from the group consisting of tungsten (W) and molybdenum (Mo), and X is selected from the group consisting of sulfur (S) and selenium (Se).

[0012] In one embodiment, the 1T'-TMD nanosheet comprises 1T' phase tungsten disulfide (1T'-WS2).

[0013] In one embodiment, the average thickness of the 1T'-TMD nanosheets ranges from 0.7 nm to 2.1 nm.

[0014] In one embodiment, the polymer matrix is ​​selected from the group consisting of polyacrylic acid, polyvinyl alcohol, polyethylene glycol, sodium polyacrylate, polyacrylamide, polyethyleneimine, polystyrene sulfonic acid, and sodium polystyrene sulfonate.

[0015] In one embodiment, the photothermal gel, in a dry state, exhibits a solar absorption rate of at least 0.9 in the wavelength range of 200 nm to 2000 nm.

[0016] In another embodiment, the photothermal gel further includes noble metal nanoparticles modified on the surface of the 1T'-TMD nanosheets, and also includes at least one semiconductor catalyst coupled to the 1T'-TMD nanosheets. The noble metal nanoparticles are silver (Ag) nanoparticles with an average particle size distribution between 5 nm and 20 nm.

[0017] According to another aspect, the present invention provides a photocatalytic-photothermal composite system for solar-driven water evaporation and VOC photodegradation. The system comprises: a hydrogel matrix containing half-metallic 1T'-TMD nanosheets integrated into a cross-linked polymer network; and at least one semiconductor catalyst in direct interfacial contact with the 1T'-TMD nanosheets to form a semiconductor / 1T'-TMD interfacial heterojunction. The interfacial heterojunction promotes charge carrier separation between the semiconductor catalyst and the 1T'-TMD nanosheets, and wherein the half-metallic 1T'-TMD nanosheets act as an electron transport medium.

[0018] The semi-metallic 1T' phase 1T'-TMD nanosheets are configured to act as an electron transport medium to promote charge carrier separation from at least one semiconductor catalyst via a built-in electric field. This composite system is configured to simultaneously perform solar-driven vapor generation and photocatalytic degradation of organic pollutants. After irradiation at 1 solar intensity for 60 minutes, the system achieves a photocatalytic degradation efficiency of at least 90% for phenol.

[0019] In one embodiment, at least one semiconductor catalyst is selected from the group consisting of graphitic carbon nitride, titanium dioxide, zinc oxide, iron oxide, bismuth halogenate, and cadmium sulfide.

[0020] In one embodiment, the mass ratio of at least one semiconductor catalyst to the 1T'-TMD nanosheet ranges from 5:1 to 50:1.

[0021] In one embodiment, the volatile organic compound includes phenol, aniline, formaldehyde, benzene, or toluene.

[0022] In one embodiment, after irradiation at 1 solar intensity for 60 minutes, the system achieves a photocatalytic degradation efficiency of phenol ranging from 80% to 99%.

[0023] In another embodiment, the system further includes a water supply assembly configured to deliver source water to the hydrogel matrix via capillary action, wherein the hydrogel matrix is ​​located at the air-water interface.

[0024] According to another aspect, the present invention provides a method for preparing a 1T'-TMD-based hydrogel, comprising: (a) heating a mixture comprising a 2H-phase TMD precursor, a potassium-based salt auxiliary agent, and a chalcogenide source under a reducing atmosphere and at a temperature of 700°C to 900°C to synthesize 1T'-phase crystals; (b) exfoliating the 1T'-phase crystals to obtain a 1T'-TMD nanosheet suspension; (c) dispersing the 1T'-TMD nanosheets in a hydrophilic polymer solution containing a crosslinking agent, and forming a pregel mixture by uniform mixing; and (d) subjecting the mixture to a flash freeze-thaw treatment to construct an interconnected submicron porous structure while maintaining the half-metallic 1T' phase. The exfoliation rate of the 1T'-TMD nanosheets is at least 80% relative to the total mass of the exfoliated nanosheets obtained from the 1T'-phase crystals.

[0025] In one embodiment, the hydrophilic polymer is selected from the group consisting of polyvinyl alcohol, polyacrylic acid, polyethylene glycol, sodium polyacrylate, polyacrylamide, polyethyleneimine, polystyrene sulfonic acid, sodium polystyrene sulfonate, and combinations thereof. The concentration of the hydrophilic polymer in the hydrophilic polymer solution ranges from 100 mg / mL to 400 mg / mL.

[0026] In one embodiment, the stripping step is performed by ultrasonic treatment in an acidic solution containing H2SO4 at a concentration of 0.1 M to 1.0 M.

[0027] In one embodiment, the potassium-based salt auxiliary is selected from the group consisting of potassium oxalate, potassium oxalate monohydrate, potassium carbonate, and potassium bicarbonate. The sulfur source is selected from the group consisting of sulfur (S) powder and selenium (Se) powder, and the 2H phase TMD precursor is selected from the group consisting of WS2 powder, MoS2 powder, WSe2 powder, and MoSe2 powder.

[0028] In one embodiment, the salt additive comprises potassium oxalate monohydrate, and the mass ratio of the 2H phase TMD precursor, the salt additive, and the sulfide source ranges from 1:0.5:1 to 1:1.5:2.

[0029] In one embodiment, the hydrophilic polymer solution comprises polyvinyl alcohol in a concentration range of 100 mg / mL to 400 mg / mL.

[0030] In one embodiment, crosslinking is performed using glutaraldehyde and an acid catalyst, wherein the concentration of the acid catalyst is maintained between 0.02 M and 0.1 M.

[0031] In one embodiment, the mixture is immediately placed in a freezer with a temperature range of -20 °C to -80 °C and kept there for 4 to 12 hours.

[0032] This invention effectively solves long-standing problems in existing solar evaporation technologies. Conventional photothermal materials often suffer from limited solar energy absorption or excessively rapid phase degradation, while the semi-metallic nature of 1T'-TMD ensures its inherent stability and wide-bandgap solar energy response. The hydrogel-interconnected porous structure promoted by 1T'-TMD provides efficient water transport and localized heat insulation, overcoming the problem of excessively rapid heat dissipation commonly found in metal-based materials. Most importantly, the high electron transport capability of the 1T' phase suppresses electron-hole recombination, solving the problem of slow carrier separation that typically hinders the efficiency of 2H-phase TMD photocatalysts.

[0033] Compared with existing technologies, this invention differs from traditional TMD systems that require complex external modification. Using 1T'-WS2 nanosheets as the intrinsic surfactant, it achieves a yield of approximately 3.6 kg m -2 h -1 It exhibits a high evaporation rate and a solar-steam conversion efficiency of 90.0%. Notably, the 1T'-TMD gel demonstrates excellent water activation capabilities, significantly reducing the water vaporization enthalpy by enriching interfacial water species. Furthermore, this invention exhibits excellent self-cleaning and anti-scaling properties, maintaining stable performance and preventing salt accumulation even under high salt concentrations (up to 20 wt%). When coupled with a photocatalyst, an unexpected synergistic effect occurs between the semi-metallic phase and the semiconductor, resulting in a phenol removal rate exceeding 98%, making this technology a robust platform for next-generation water purification. Attached Figure Description

[0034] Embodiments of the invention are described in more detail below with reference to the accompanying drawings, in which:

[0035] Figure 1 A schematic diagram depicting the gel preparation process of the present invention is shown.

[0036] Figure 2A Show K x Scanning electron microscope (SEM) images of WS2 crystals and 2H-WS2 powder. Figure 2B Demonstrating the prepared K x SEM images of the WS2 chip and elemental distribution diagrams of the corresponding WL, SK and KK signals, as well as their overlapping distribution diagrams. Figure 2C Show K x X-ray diffraction (XRD) patterns of WS2 crystals and 2H-WS2 powder. Figure 2D Show K x Raman spectra of WS2 crystals and 2H-WS2 powder.

[0037] Figure 3ATransmission electron microscopy (TEM) images of the exfoliated 1T'-WS2 and 2H-WS2 nanosheets are shown. Figure 3B Atomic force microscopy (AFM) images of the exfoliated 1T'-WS2 and 2H-WS2 nanosheets are shown. Figure 3C High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) images of representative 1T'-WS2 nanosheets are shown, with the corresponding selected area electron diffraction (SAED) patterns displayed in the inset.

[0038] Figure 4A TEM images of representative 2H-WS2 nanosheets are shown. Figure 4B High-resolution transmission electron microscopy (HRTEM) images of 2H-WS2 nanosheets are shown, with the corresponding fast Fourier transform (FFT) spectra displayed in the inset.

[0039] Figure 5A Raman spectra (au, arbitrary units) of the exfoliated 1T'-WS2 and 2H-WS2 nanosheets are shown. Figure 5B The X-ray photoelectron spectroscopy (XPS) spectra of the exfoliated 1T'-WS2 and 2H-WS2 nanosheets are shown. Figure 5C Show K x K 2p XPS spectra of WS2 crystals and the resulting 1T'-WS2 nanosheets.

[0040] Figure 6A The UV-Vis-NIR absorption spectra of the exfoliated 1T'-WS2 and 2H-WS2 nanosheets are shown. Figure 6B The fluorescence spectra of the obtained 1T'-WS2 and 2H-WS2 nanosheets are shown.

[0041] Figure 7A Transient absorption pseudo-color images of 2H-WS2 nanosheets and 1T'-WS2 nanosheets are displayed. Figure 7B The time-resolved transient absorption spectra (mOD) of 2H-WS2 nanosheets and 1T'-WS2 nanosheets under 380 nm excitation are shown.

[0042] Figure 8A The transient absorption kinetics of 1T'-WS2 nanosheets are shown at a pump wavelength of 380 nm and a probe wavelength as indicated. The solid line represents the triple-exponential decay fitting curve after convolution with the Gaussian response function. Figure 8B The transient dynamics of 2H-WS2 nanosheets at 532 nm and 630 nm, and the transient dynamics of 1T'-WS2 nanosheets at 850 nm are shown.

[0043] Figure 9AThe top and side views of the 1T'-WS2 monolayer are depicted, with the unit cell outlined in black, along with the corresponding element-resolved band structure and projected density of states. Figure 9B Depict top and side views of the 2H-WS2 bilayer, with unit cells outlined in black, and corresponding elemental projected band structure and projected density of states.

[0044] Figure 10A The reflectance of 1T'-WS2 and 2H-WS2 from monolayer to trilayer and bulk structures is shown using density functional theory (DFT). Figure 10B The absorption coefficients of 1T'-WS2 and 2H-WS2 from monolayer to trilayer and bulk structures are shown.

[0045] Figure 11A Optical photographs and cross-sectional SEM images of the prepared 1T'-WS2 gel are shown. Figure 11B Optical photographs and cross-sectional SEM images of the prepared 2H-WS2 gel are shown. Figure 11C The SEM characterization of the pure gel is shown, and its photograph is shown in the illustration. Figure 11D The elemental distribution diagram of the 1T'-WS2 gel is shown.

[0046] Figure 12A Fourier transform infrared (FTIR) spectra of 1T'-WS2, 2H-WS2 gels and pure gel are shown. Figure 12B Raman spectra of 1T'-WS2 gel, 2H-WS2 gel and pure gel are shown. Figure 12C The W 4f XPS spectrum of the 1T'-WS2 gel is shown.

[0047] Figure 13A The UV-Vis-NIR absorption spectra of 1T'-WS2 gel and 2H-WS2 gel in the wetted state are shown. Figure 13B and 13C The transmission and reflection spectra of 1T'-WS2 gel, 2H-WS2 gel and pure gel in the wetted state are shown.

[0048] Figure 14A , 14B The absorption, transmission, and reflection spectra of 1T'-WS2 gel, 2H-WS2 gel, and pure gel in the dry state are shown in 14C.

[0049] Figure 15 The temperature of the wetted gel top surface and the underlying bulk water under one solar irradiation is shown as a function of time.

[0050] Figure 16 Infrared thermographs of 2H-WS2 gel and 1T'-WS2 gel from 0 to 60 minutes under one solar irradiation are shown.

[0051] Figure 17 The mass changes of bulk water, pure gel, 2H-WS2 gel and 1T'-WS2 gel under one solar irradiation are shown.

[0052] Figure 18 The evaporation rates and photovaporization efficiencies of bulk water, pure gel, 2H-WS2 gel, and 1T'-WS2 gel under one solar irradiation are shown.

[0053] Figure 19 This paper presents a comparison of water evaporation rates in evaporators of TMDs with different phase structures.

[0054] Figure 20 Thermochromatograms of pure gel, 2H-WS2 gel and 1T'-WS2 gel are shown.

[0055] Figure 21A The physical in-situ attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectra of hydrated 1T'-WS2 and 2H-WS2 over time are shown. Figure 21B The Gaussian fit of the OH stretching vibration band at 28 seconds is shown, indicating weakly hydrogen-bonded water (3350-3650 cm⁻¹). -1 ) and strongly hydrogen-bonded water (3200-3350 cm) -1 ).

[0056] Figure 22A , 22B The IW / FW ratios are shown in Figure 22C, derived from the Raman spectra of bulk water, pure gel, 2H-WS2 gel, and 1T'-WS2 gel.

[0057] Figure 23 The water evaporation rate of 1T'-WS2 gel under different salinity conditions is demonstrated.

[0058] Figure 24A Raman spectra of 1T'-WS2 gel after stability testing are shown. Figure 24B XPS spectra of 1T'-WS2 gel after stability testing are shown.

[0059] Figure 25A Demonstrates the compressive deformation of 1T'-WS2 gel at 90% of its maximum compressive strain. Figure 25B The stress-strain curves are shown after 50 loading-unloading cycles at 50% of the maximum compressive strain. The inset shows gel photographs before and after the 100th loading cycle.

[0060] Figure 26A , 26BSEM, TEM and Raman characterization of MoS2, MoSe2 and WSe2 materials with 1T' phase and 2H phase are shown in 26C.

[0061] Figure 27A , 27B The absorption spectra, mass changes, and water evaporation rates of the 1T' phase and 2H phase TMD gels (WSe2, MoS2, MoSe2) under one sun irradiation are shown in Figure 27C.

[0062] Figure 28A Draw a schematic diagram of the water collection device. Figure 28B Photos showcasing water collection systems in actual outdoor applications.

[0063] Figure 29 It shows the changes in ambient temperature, solar flux, hourly water production rate, and cumulative water production over time during daytime operation.

[0064] Figure 30 Infrared thermographs of 1T'-WS2 gel during operation are shown.

[0065] Figure 31 The concentrations of the main cations and anions in seawater before and after purification are displayed.

[0066] Figure 32 The removal performance of 1T'-WS2 gel on heavy metals before and after solar distillation is demonstrated.

[0067] Figure 33 The UV-Vis spectra of methyl orange and methylene blue aqueous solutions before and after solar distillation are shown, and the corresponding photographs are shown in the illustrations.

[0068] Figure 34A The HRTEM image and energy dispersive spectroscopy (EDS) elemental mapping diagram of the 1T′-WS2 / g-C3N4 composite material are shown. Figure 34B XPS spectra comparison of g-C3N4 nanosheets and 1T′-WS2 / g-C3N4 composite material are shown.

[0069] Figure 35A and 35B The FTIR and Raman spectra of the composite materials 1T′-WS2 / g-C3N4 and 2H-2H-WS2 / g-C3N4 are shown. Figure 35C Display the transient photocurrent (it) response curve. Figure 35D The Nyquist diagram shows a solar evaporation and phenol degradation device used in a closed system. Figure 35E The photoluminescence spectrum of the same device is shown. Figure 35F A schematic diagram of the device is shown. Figure 35GThe phenol removal efficiency of 2H-WS2 gel, 1T'-WS2 gel, 2H-WS2 / g-C3N4 gel and 1T′-WS2 / g-C3N4 gel is compared. Figure 35H The mass change curve of 1T′-WS2 / g-C3N4 gel under one sun irradiation is shown.

[0070] Figure 36A , 36B The absorption, transmission, and reflection spectra of 1T'-WS2 gel, 2H-WS2 gel, and pure gel in a wet state are shown in Figure 36C.

[0071] Figure 37A , 37B The absorption, transmission, and reflection spectra of 1T'-WS2 gel, 2H-WS2 gel, and pure gel in a dry state are shown in Figure 37C. Detailed Implementation

[0072] definition

[0073] Throughout this specification, unless the context otherwise requires, the word “comprise” or variations such as “comprises” or “comprising” should be understood to imply inclusion of the stated whole or group of wholes, but not to exclude any other whole or group of wholes. It should also be noted that in this disclosure and particularly in the claims and / or paragraphs, terms such as “comprises,” “comprised,” and “comprising” may have the meaning attributed to them under U.S. patent law, for example, allowing for elements not expressly listed but excluding elements present in the prior art or affecting the essential or novel characteristics of the invention.

[0074] Furthermore, throughout this specification and claims, unless the context otherwise requires, the word "include" or variations thereof, such as "includes" or "including," shall be understood to imply inclusion of the stated whole or group of wholes, but not to exclude any other whole or group of wholes.

[0075] As used herein and unless otherwise defined, the terms “substantially,” “basically,” “approximately,” and “about” are used to describe and explain small variations. When used in conjunction with an event or situation, the terms may cover instances where the event or situation occurred precisely or instances where the event or situation was close to occurring. For example, when used in conjunction with a numerical value, the terms may cover a range of variation less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%.

[0076] References to "an embodiment," "an example embodiment," "exemplary embodiment," etc., in this specification indicate that the described embodiment may include a specific feature, structure, or characteristic, but not every embodiment necessarily includes that specific feature, structure, or characteristic. Furthermore, such phrases do not necessarily refer to the same embodiment. Moreover, when a specific feature, structure, or characteristic is described in connection with an embodiment, it is assumed that the effect of such feature, structure, or characteristic in conjunction with other embodiments is within the knowledge of those skilled in the art, whether explicitly described or not.

[0077] In the preparation methods described herein, steps may be performed in any order without departing from the principles of the invention, except where the time or order of operations is explicitly stated. A statement in a claim that implies performing a step first, followed by several other steps, should be interpreted as meaning that the first step is performed before any other steps, but the other steps may be performed in any suitable order unless the order is further stated in the other steps. For example, a claim element stating "steps A, B, C, D, and E" should be interpreted as meaning that step A is performed first, and step E is performed last, and steps B, C, and D may be performed in any order between steps A and E, and such order still falls within the literal scope of the claimed process. A given step or subset of steps may also be repeated. Furthermore, unless the explicit claim language states that the specified steps are performed separately, the specified steps may be performed simultaneously.

[0078] The term "1T phase" refers to a distorted octahedral coordination geometry of TMD characterized by symmetry breaking relative to the ideal 1T structure. This phase typically exhibits half-metallic electronic properties and involves periodic lattice distortions that lead to metal-metal bonding chains (e.g., WW chains in WS2).

[0079] The term "transition metal chalcogenide" or "TMD" refers to a class of two-dimensional materials with the chemical formula MX2, where M is a transition metal atom (e.g., W, Mo) and X is a chalcogenide atom (e.g., S, Se, Te). This structure consists of a single layer of M atoms sandwiched between two layers of X atoms.

[0080] The term "semi-metal" refers to an electronic structure characterized by a small overlap between the conduction band bottom and the valence band top, resulting in a band gapless structure. This property is advantageous for high carrier density and broadband optical absorption across the entire solar spectrum.

[0081] The term "interfacial heterojunction" refers to the physical and electronic contact region formed between 1T'-TMD nanosheets and a semiconductor catalyst. This junction is configured to generate an embedded electric field to drive the separation of photogenerated electron-hole pairs.

[0082] The term "electron transport medium" refers to a material or structural component in a photocatalytic system that promotes the transfer and delocalization of photogenerated electrons from coupled semiconductors at the interface, thereby improving charge carrier separation efficiency and suppressing electron-hole recombination.

[0083] The term "interconnected porous framework" refers to a three-dimensional network structure within a polymer matrix, characterized by a series of physically interconnected open pores that allow for continuous fluid transport throughout the hydrogel mass via capillary action.

[0084] Other definitions of the selected terms used herein can be found in the specific description of the invention and apply throughout. Unless otherwise defined, all other technical terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0085] In the following description, 1T'-TMD, the improved stripping method, and its specific application in a photothermal-driven water evaporation and photocatalytic degradation system are illustrated as preferred embodiments. It will be apparent to those skilled in the art that modifications, including additions and / or substitutions, can be made without departing from the scope and spirit of the invention. To avoid obscuring the core of the invention, some specific details may be omitted; however, this specification is intended to enable those skilled in the art to practice the disclosed technical solutions without excessive experimentation.

[0086] Solar interface steam generation is a highly attractive approach for seawater desalination and wastewater purification; however, its efficiency is still limited by the weak photothermal reaction and poor water activation capabilities of traditional materials.

[0087] This invention provides a comprehensive platform for the synthesis and application of 1T' phase transition metal chalcogenide (1T'-TMD) gels, specifically designed for high-efficiency solar-driven water purification and environmental remediation. To overcome the thermodynamic instabilities and synthesis challenges associated with traditional metallic TMD phases, this invention utilizes a one-pot salt-assisted strategy to prepare stable, high-purity 1T' phase crystals. This method achieves precise phase control by embedding specific ions (e.g., potassium ions) into the interlayer gaps, thereby stabilizing the coordination of distorted octahedral (1T') structures and producing half-metal materials with superior electronic properties.

[0088] Furthermore, this invention introduces an efficient and scalable chemical exfoliation method that utilizes simple ultrasonic treatment in an acidic medium to separate the 1T' phase crystal layer into single-layer or few-layer nanosheets. This process overcomes the industrial limitation of low exfoliation yield commonly found in semiconducting 2H phase TMDs.

[0089] In one embodiment, high-purity 1T' phase TMD crystals are synthesized using a salt-assisted method. A mixture comprising 2H phase TMD precursor powder, a salt auxiliary agent (such as potassium oxalate monohydrate), and a sulfide source (such as sulfur powder or selenium powder) is prepared, wherein the molar ratio of the three is preferably about 1:1.1:10. The synthesis is carried out under controlled conditions (e.g., a tube furnace) and a reducing atmosphere (e.g., a H2 / Ar mixture) at temperatures ranging from 700°C to 900°C (typically 800°C) for a duration sufficient to ensure the phase transition.

[0090] In another embodiment, 1T'-TMD nanosheets were prepared by sonicating the synthesized crystals in an acidic solution (e.g., 0.5 M H₂SO₄), which facilitates interlayer expansion and delamination. Compared to conventional 2H phase exfoliation, this chemical exfoliation method achieves significantly higher yields, up to 90.8%. High-quality ultrathin nanosheets with an average thickness of approximately 1.1 nm were successfully separated by multi-stage centrifugation purification of the resulting suspension.

[0091] In one embodiment, the 1T'-TMD used in this invention includes, but is not limited to, 1T'-phase tungsten disulfide (1T'-WS2), 1T'-phase molybdenum disulfide (1T'-MoS2), 1T'-phase molybdenum diselenide (1T'-MoSe2), 1T'-phase tungsten diselenide (1T'-WSe2), and combinations or derivatives thereof. The 1T'-TMD material is characterized by a distorted octahedral coordinated half-metallic electronic structure, which provides inherent advantages in broadband solar light absorption and efficient carrier transport compared to conventional semiconducting 2H counterparts.

[0092] For example, by directly ultrasonically treating the parent K in a dilute acid medium (such as H2SO4). xWS2 crystals were successfully delaminated into ultrathin 1T'-WS2 nanosheets. This chemical exfoliation process utilizes K... x The increased interlayer spacing within the WS2 crystals stems from the supporting effect of residual potassium ions during salt-assisted synthesis. These residual ions facilitate excellent solvent penetration during ultrasonic treatment, thereby achieving highly efficient delamination. Consequently, this invention achieves a high exfoliation yield of approximately 90.8%. This yield represents a significant increase of over 100 times compared to the mere 0.83% yield of the 2H-WS2 control powder under the same conditions. This high-yield and scalable preparation method ensures a stable supply of the inherently active photothermal agent, which exhibits excellent uniform dispersibility in aqueous environments. This facilitates its seamless integration into a multifunctional hydrogel matrix, enabling simultaneous dual-effect treatment through the synergistic effect of water evaporation and contaminant degradation.

[0093] Furthermore, the 1T'-TMD nanosheets of the present invention may comprise ternary or quaternary alloys of transition metals and chalcogenides, the general formula of which is derived from MS. 2x Se 2(1-x) The expression indicates that M is a transition metal (such as W or Mo), and x ranges from 0 to 1. These phase-engineered materials may further contain residual ions (such as potassium ions) located within the interlayer spaces; these ions stabilize the 1T' crystal structure and promote the high-yield delamination of the material into monolayers or few-layer nanosheets. Such high-purity 1T'-TMDs maintain uniform dispersion in both aqueous and organic solvents, ensuring their flexible integration into various hydrogel matrices to achieve a synergistic effect of water evaporation and pollutant degradation.

[0094] Integrating semi-metallic 1T'-TMD nanosheets into hydrogel systems significantly enhances solar absorption across a broad wavelength range of 200–2000 nm; this is attributed to their unique electronic and structural properties, such as long-lived carrier absorption. Compared to conventional semi-semiconductor 2H counterparts, these 1T'-TMD-based gels exhibit superior photothermal conversion efficiency and faster evaporation rates, even at ultra-low nanosheet loadings of approximately 0.26 wt%. Furthermore, the interconnected porous structure of the hydrogel matrix, facilitated by 1T'-TMD, effectively prevents salt accumulation and surface fouling under high salinity conditions up to 20 wt%. These synergistic photothermal and structural properties enable 1T'-TMD gels to demonstrate extremely high performance in advanced solar-driven water purification and environmental remediation applications.

[0095] In one embodiment, the hydrogel system of the present invention comprises a polymer matrix configured to support 1T'-TMD nanosheets. The polymer matrix may be selected from the group consisting of polyvinyl alcohol, polyacrylic acid, polyethylene glycol, sodium polyacrylate, polyacrylamide, polyethyleneimine, polystyrene sulfonic acid, or combinations thereof. This polymer matrix has several key functions: providing a robust, interconnected porous framework to facilitate rapid capillary transport of water; providing thermal insulation to confine heat to the evaporation interface; and effectively anchoring the 1T'-TMD nanosheets to prevent their aggregation. In some embodiments, the concentration of the polymer in the precursor solution ranges from 100 g / L to 300 g / L.

[0096] In some embodiments, the concentration of 1T'-TMD nanosheets in the hydrogel ranges from 0.05 wt% to 8.0 wt%, preferably from 0.1 wt% to 3.0 wt%.

[0097] In some embodiments, the 1T'-TMD-based hydrogel is configured for applications selected from: seawater desalination, industrial wastewater treatment, heavy metal recovery, solar-driven sterilization, and thermoelectric power generation.

[0098] On the other hand, the present invention provides a multifunctional composite system by coupling 1T'-TMD with at least one semiconductor catalyst to achieve simultaneous solar-driven evaporation and photocatalytic degradation of pollutants. The semiconductor catalyst may include, but is not limited to, graphitic carbon nitride (g-C3N4), titanium dioxide (TiO2), zinc oxide (ZnO), iron oxide (Fe2O3), or cadmium sulfide (CdS).

[0099] In one embodiment, the amount of the semiconductor catalyst ranges from 100 mg to 500 mg. The half-metallic 1T' phase acts as a high-mobility electron transport medium and forms a built-in electric field with the semiconductor catalyst to suppress electron-hole recombination and significantly improve the degradation efficiency of pollutants such as VOCs, industrial dyes, and pesticides.

[0100] In another aspect, the present invention provides a method for preparing 1T'-TMD-based hydrogels, comprising the following steps:

[0101] (a) Synthesis of 1T' phase crystals: 2H phase TMD precursor, salt additives and chalcogen source were mixed and then heated in a controlled atmosphere to induce phase transformation into high-purity 1T' phase crystals.

[0102] (b) High-yield exfoliation: The synthesized crystals are dispersed in an acidic solution and subjected to ultrasonic treatment to delaminate (or exfoliate) the crystal layers into single-layer or few-layer 1T'-TMD nanosheets;

[0103] (c) Hydrogel integration: The exfoliated nanosheets are introduced into a polymer solution, and then a crosslinking agent and an initiator are added to form a hydrogel matrix through a gelation process;

[0104] (d) Phase-controlled curing: The resulting mixture is subjected to at least one freeze-thaw cycle to establish an interconnected porous structure while maintaining the semi-metallic phase of the TMD nanosheets;

[0105] The exfoliation yield of the 1T'-TMD nanosheets is at least 80% relative to the total mass of exfoliated nanosheets obtained from the 1T' phase crystal.

[0106] In the following description, specific details are provided to provide a comprehensive description of various embodiments of the invention for illustrative purposes and are not intended to be limiting.

[0107] Example

[0108] Example 1 - Materials and Methods

[0109] 1T′-K x Synthesis of WS2 crystals

[0110] 1T' TMD crystal (e.g., 1T′-K) x The synthesis of WS2 is carried out via a salt-assisted thermochemical process. A precursor mixture is prepared by combining 2H-phase TMD powder, a salt auxiliary agent (e.g., K2C2O4·H2O), and a chalcogen source (e.g., sulfur powder). The weight ratio of the 2H-phase TMD powder, salt auxiliary agent, and chalcogen source ranges from 1:0.5:1 to 1:1.5:2. The mixture is milled to achieve homogeneity and then heat-treated in a reaction chamber. It is preferable to use an inert gas to purge the air from the environment. The reaction is carried out at a temperature of 700-900 °C (preferably about 800 °C) and maintained in a reducing atmosphere (e.g., a mixture of H2 (30%) / Ar (70%)) for 2-6 hours.

[0111] After cooling, the product is washed with deionized water until a substantially neutral pH value is reached (e.g., pH 6.0 to 8.0). The product may be further immersed in water and then dried to obtain high-purity 1T' phase crystals.

[0112] Preparation of 1T'-WS2 nanosheets and 2H-WS2 nanosheets

[0113] To synthesize 1T'-WS2 nanosheets and 2H-WS2 nanosheets, the synthesized K xWS2 crystals and 2H-WS2 powder are dispersed in an acidic solution such as H2SO4. In some embodiments, the concentration of the acidic solution ranges from 0.1 M to 5.0 M (e.g., about 0.5 M). The resulting mixture is sonicated for a duration sufficient to induce delamination, typically ranging from 5 to 30 minutes. In a preferred embodiment, the sonication is performed at a relatively low power setting to maintain the large lateral dimensions of the nanosheets and the integrity of the semi-metallic phase. Following sonication, the suspension undergoes a multi-stage purification process to separate high-quality nanosheets. In one embodiment, the process includes: (a) solvent exchange: centrifuging the suspension at high speed, for example, between 8,000 and 15,000 rpm (e.g., about 10,000 rpm), followed by replacing the acidic supernatant with deionized water (e.g., Milli-Q water); and (b) size screening: further centrifuging the resulting suspension at lower speeds, for example, between 1,000 and 3,000 rpm (e.g., about 2,000 rpm). Collect the supernatant containing the peeled single-layer or few-layer nanosheets, while removing the unpeeled or partially peeled precipitates.

[0114] Preparation of 1T'-WS2 gel, 2H-WS2 gel and pure gel

[0115] The core of preparing the 1T' phase TMD gel lies in introducing exfoliated nanosheets into a crosslinked polymer network. The process begins with the preparation of a polymer solution, in which a hydrophilic polymer such as polyvinyl alcohol is fully dissolved in an aqueous medium. In some embodiments, the concentration of the polymer solution ranges from 100 mg / mL to 400 mg / mL (e.g., about 150 mg / mL), achieved by heating the mixture (e.g., at 90 °C to 100 °C) until complete dissolution. The gelation process is initiated by adding a crosslinking agent. In one embodiment, a crosslinking agent such as glutaraldehyde is introduced into the polymer solution. The mixture is typically mechanically stirred and sonicated for a duration sufficient to ensure uniform distribution of the components. To simultaneously achieve photothermal functionality and structural integrity, 1T' phase TMD nanosheets and an acid catalyst (e.g., hydrochloric acid) are integrated into the mixture. In some embodiments, the concentration of the acid catalyst is maintained between about 0.02 M and 0.1 M. The resulting precursor solution is then subjected to a curing and structure-forming process, which includes maintaining the solution at ambient temperature for a period sufficient to allow crosslinked network formation (e.g., an overnight gelation phase). After initial gelation, the resulting hydrogel is immersed in a solvent (e.g., deionized water) to promote solvent exchange and swelling, thereby removing unreacted species and obtaining the desired porous structure and degree of hydration before characterization or application.

[0116] like Figure 1As shown, a solution of 0.3 g polyvinyl alcohol was prepared by dissolving 0.3 g in 20 mL of deionized water at 95 °C for 1 hour, yielding a solution of 15 mg / mL. -1 A polyvinyl alcohol aqueous solution was prepared. To initiate crosslinking, 12.5 μL of glutaraldehyde solution was introduced into 10 mL of polyvinyl alcohol solution placed in a silica gel container. The mixture was magnetically stirred for 5 minutes, followed by sonication in a water bath ultrasonic cleaner for 10 minutes. Next, 40 μL of 1.2 M HCl solution and 1 mL of 1T'-WS2 suspension were added, and the mixture was stirred for 2 minutes to ensure uniform dispersion. The solution was then left at room temperature overnight, followed by thawing by immersion in room temperature deionized water. The resulting hydrogel was then swollen in deionized water and used for further characterization and application. For comparison, a 2H-WS2-based hydrogel (2H-WS2 gel) was prepared using the same procedure.

[0117] Density functional theory calculations

[0118] All first-principles calculations based on density functional theory (DFT) were performed using the Vienna Ab InitioSimulation Package (VASP). Grimme's D3 dispersion correction method was employed to account for van der Waals interactions between the WS2 layers. The calculations used the generalized gradient approximation (GGA-PBE) method with Perdew-Burke-Ernzerhof functionals, and the projected fused wave (PAW) method was used to describe electron-ion interactions. Furthermore, an energy cutoff of 400 eV was set. To ensure the accuracy of optical properties, the convergence criterion for self-consistent calculations was set to an energy change of less than 10 eV. -8 eV. Furthermore, all calculations incorporated spin-orbit coupling (SOC) effects to fully compensate for the influence of relativistic effects on the electronic structure and optical transitions. Optical properties were derived from frequency-dependent dielectric functions obtained through a random phase approximation. The Brillouin zone was sampled using a K-point grid centered at the γ point, corresponding to a reciprocal lattice resolution of 2π × 0.025 / Å. Optical property data were post-processed using VASPKIT software. Ab initio molecular dynamics (AIMD) simulations were performed under an NVT canonical ensemble at 300 K, with temperature controlled using a Nosé-Hoover chain bath and a time step of 1 fs. Additionally, the distribution of hydrogen bond density with bond length and distance from the surface was evaluated using a Gaussian-type kernel function via kernel density estimation (KDE).

[0119] Example 2 - Characterization of 1T'-WS2 nanosheets and 2H-WS2 nanosheets

[0120] The morphology and composition of the synthesized 1T' phase crystal were characterized to verify its structural integrity and phase purity. Figure 2A As shown in the SEM image, K x WS2 crystals exhibit a plate-like morphology with lateral dimensions reaching hundreds of micrometers; compared to conventional 2H phase powders with rougher surfaces, these crystals display a brighter appearance. EDS data indicate that these crystals contain embedded potassium, for example, an atomic percentage of approximately 5% to 15% (e.g., 9.7%), which helps stabilize their half-metallic phase. Figure 2B ).

[0121] XRD patterns and Raman spectroscopy further confirmed the phase transformation. For example... Figure 2C As shown, the XRD diffraction peaks of the obtained crystal are consistent with the simulated 1T'-WS2, and exhibit a significant shift relative to the 2H phase. The Raman spectrum reveals a characteristic 1T' phase vibrational mode, specifically located at approximately 112 cm⁻¹. -1 181 cm -1 240 cm -1 270 cm -1 317 cm -1 and 408 cm -1 The diffraction peak at 352 cm⁻¹; simultaneously, 352 cm⁻¹ -1 and 420 cm -1 The absence of the characteristic peak of the 2H phase confirms the extremely high phase purity. Figure 2D ).

[0122] The chemical exfoliation efficiency of the 1T' phase crystals exhibits a significant technological advantage over the 2H phase. Following ultrasonic treatment in an acidic medium, the 1T' phase material formed a high-concentration, stable black dispersion, achieving a high exfoliation yield of at least 80% (e.g., approximately 90.8%). This represents an improvement of over 100 times compared to the 2H counterpart (e.g., approximately 0.83%) (Table 1). This superior efficiency is attributed to the intercalated cations (e.g., potassium ions), which widen the interlayer spacing, thereby promoting solvent penetration and exfoliation. The process is easily scaled up, enabling large-volume production of concentrations up to 10 g L⁻¹. -1 1T' phase TMD dispersion.

[0123] Table 1 - Inductively Coupled Plasma Mass Spectrometry (ICP-MS) Results of WS2 Concentration in Exfoliated Samples

[0124] As shown in the TEM image, the obtained 1T'-WS2 nanosheets have a satin-like ultrathin sheet morphology, with lateral dimensions reaching several micrometers. Figure 3A AFM images show that the average thickness of the 1T'-WS2 nanosheets is 1.1 ± 0.2 nm. Figure 3B The thickness of the 2H-WS2 nanosheets is 1.9 ± 0.4 nm. Aberration-corrected HAADF-STEM images reveal a zigzag chain-like arrangement, while the corresponding SAED patterns show unique diffraction patterns characteristic of the 1T' phase. Figure 3C This is consistent with the hexagonal symmetric diffraction pattern of 2H-WS2 ( Figures 4A-4B (This creates a contrast.)

[0125] Raman spectroscopy further confirmed the phase purity of the 1T'-WS2 nanosheets. Figure 5A ). Observed at 130 cm -1 205cm -1 256 cm -1 310 cm -1 and 408 cm -1 Five unique Raman peaks at the 1T' phase confirm its 1T' phase crystal structure, which is distinctly different from the 2H phase counterpart. This observation further demonstrates the extremely high phase purity of the synthesized nanosheets.

[0126] Spectroscopic methods were used to further distinguish the differences in electronic and optical properties between the 1T' phase TMD nanosheets and the 2H phase. For example... Figure 5B As shown, XPS data displays its W 4f 5 / 2 and W 4f 7 / 2 The binding energy shifted by approximately 0.8 eV relative to the 2H phase, consistent with the half-metallic properties of the 1T' structure. Furthermore, no potassium residue was detected in the exfoliated nanosheets. Figure 5C ).

[0127] Optical absorption properties further distinguished the two phases: 2H-WS2 exhibited a distinct exciton resonance peak in the visible light region, while 1T'-WS2 showed a featureless broadband response. Figure 6A This indicates that it possesses delocalized electronic states. Fluorescence spectrum ( Figure 6B The results showed that the semiconductor 2H phase had a strong emission signal, while no identifiable signal was detected in 1T'-WS2; this confirms that radiative recombination is suppressed and indicates that nonradiative energy dissipation dominates in the half-metallic phase.

[0128] Example 3 - Ultrafast Carrier Dynamics and Photothermal Mechanism

[0129] To elucidate the excellent photothermal conversion mechanism of the half-metal 1T' phase, its carrier relaxation dynamics were analyzed using femtosecond transient absorption spectroscopy (fs-TAS). 1T'-WS2 and 2H-WS2 samples were excited using pump pulses (e.g., a center wavelength of 380 nm), and detected using wide-band probe pulses (e.g., 460-997 nm) to acquire differential absorption spectra (ΔA(λ)). ΔA(λ) is defined as: ΔA(λ) = A(λ) - A0(λ), where A(λ) and A0(λ) represent the absorbance in the excited (pumped) and unexcited (unpumped) states, respectively.

[0130] like Figures 7A-7B As shown, the transient spectrum of 2H-WS2 reveals complex exciton reactions. The strong ΔA feature appearing at approximately 630 nm corresponds to ground-state bleaching (GSB) of the A exciton and lasts for more than 1 nanosecond; while the secondary bleaching peak at approximately 532 nm originates from the B exciton. Both originate from the energy state filling effect caused by photoexcited carriers. In addition, two excited-state absorption (ESA) features are also observed: one at 610–630 nm, attributed to transitions from intermediate states; and another at 650–670 nm, originating from hot carrier absorption into higher conduction band levels. In contrast, 1T′-WS2 ( Figures 7A-7B The 1T′ phase exhibits a significant ESA characteristic peak at 550 nm, and this signal can be sustained for more than 1 nanosecond, fully demonstrating the high-density intermediate state characteristics brought about by its delocalized electronic structure. This persistent ESA response indicates that it possesses a prolonged thermalization process and efficient nonradiative dissipation characteristics. In the longer detection wavelength range (750-950 nm), the signal contains dual contributions from both negative and positive signals: the negative signal component originates from the bleaching effect of localized surface plasmon resonance (LSPR), while the coexisting positive signal features reflect excited-state absorption associated with hot carrier redistribution. The semi-metallicity of the 1T′ phase promotes a strong plasmon reaction driven by the collective oscillation of free carriers. This mechanism enables ultrafast nonradiative relaxation, resulting in a significantly stronger thermal effect than the conventional exciton recombination pathways commonly found in semiconductor phases. By preferentially utilizing these fast nonradiative decay channels, the 1T′-TMD can convert absorbed solar energy into localized thermal energy more quickly and efficiently.

[0131] To further quantify the relaxation behavior of charge carriers, this example performs multi-exponential fitting on the transient absorption kinetics curve. The fitting results are as follows: Figures 8A-8BAs shown in Table 2, for 2H-WS2, the transient signals at 532 nm and 630 nm are dominated by ultrafast decay, with lifetimes of 1.48 ps (77.9%) and 2.27 ps (81.8%), respectively, indicating that carriers are rapidly captured and undergo nonradiative recombination. In addition to the main components, this material also contains a small amount of long-lived components: τ2 and τ3 at 532 nm are 14.98 ps and 1070.9 ps, respectively; and τ2 and τ3 at 630 nm are 30.8 ps and 406.1 ps, respectively. In stark contrast, the carrier dynamics of 1T′-WS2 exhibit a dual relaxation path. At 550 nm, its transient response consists of three consecutive rising components, with corresponding lifetimes of 3.82 ps (27.3%), 72.3 ps (28.8%), and 1331.1 ps (43.9%), respectively. This gradual signal enhancement reflects the stepwise occupancy of conduction band intermediate states by electrons and the resulting sustained excited-state absorption. This confirms the existence of efficient carrier accumulation and long-lived non-radiative dissipation processes in the system. At 850 nm, the transient absorption kinetics are dominated by a fast negative signal component with a lifetime of approximately 4.5 ps, accounting for nearly 68% of the total signal contribution, indicating that the photoinduced bleaching signal is rapidly recovered through a hot carrier cooling process. Furthermore, a minor positive signal contribution (24%) appears at approximately 1.4 ps, attributable to excited-state absorption and in-band scattering. A second positive signal contribution (24%) also appears at approximately 1.4 ps, attributable to excited-state absorption and in-band scattering. Additionally, a long-lived positive signal background with a characteristic lifetime of approximately 0.56 ns (8%) is observed, reflecting lattice heating and thermal diffusion processes in the system. In summary, the above results demonstrate that photoexcited carriers in 1T′-WS2 rapidly dissipate energy into the lattice within a picosecond timescale, thereby achieving efficient nonradiative recombination (or nonradiative relaxation) and providing microscopic mechanism support for its excellent photothermal conversion performance.

[0132] Table 2 - TAS experimental fitting parameters of 2H-WS2 and 1T′-WS2 at different detection wavelengths under 380 nm excitation.

[0133] Example 4 - First-principles electronic structure and optical property characterization

[0134] To further elucidate the intrinsic photothermal potential of the half-metallic phase, this example employs a unit cell model for first-principles calculations to compare the electronic structure and optical properties of 1T′-WS2 and 2H-WS2. Figures 9A-9BThe band structure and projected density of states (PDOS) calculations show significant differences between the two phases. The 2H phase exhibits a clear band gap and sharp band tails (or band edge states), consistent with the significant exciton resonance observed in experimental spectra.

[0135] In contrast, 1T′-WS2 exhibits semimetallic characteristics, possessing delocalized states and a continuous density of states across the Fermi level. This electronic configuration is in perfect agreement with experimental results showing that the material lacks exciton characteristics and exhibits broadband transient responses. Simulated optical spectra ( Figure 10A The results show that the strong absorption of the 2H phase is mainly concentrated near the edge of the ultraviolet band, while the 1T′ phase maintains excellent broadband absorption characteristics from the visible to the infrared region, reflecting its metalloid characteristics. Further analysis yielded the corresponding reflectance spectra. Figure 10B This has been confirmed.

[0136] Thickness-dependent calculations further demonstrate that 1T′-WS2 nanosheets with few-layer structures (such as monolayers to trilayers) exhibit more significant absorption enhancement characteristics than bulk materials. In summary, the theoretical analysis results collectively confirm that the intrinsic electronic structure of 1T′-WS2 provides a fundamental technological advantage for its efficient solar energy harvesting and photothermal conversion across a wide spectral range.

[0137] Example 5 - Hydrogel Characterization

[0138] This embodiment evaluates the structural and morphological characteristics of the 1T′ phase TMD gel to determine its suitability for solar-driven water evaporation applications. Figure 11A As shown in the optical photographs and SEM images, the 1T′-WS2 gel appears black and has a highly porous structure. This interconnected network not only facilitates rapid capillary transport of water but also extends the optical path through multiple reflections and reabsorptions within the gel matrix. In contrast, the 2H-WS2 gel is dark green and has fewer interconnected pores. Figure 11B Pure PVA gel is white, with a rough surface and shallow pores. Figure 11C Element mapping analysis () Figure 11D The results show that W and S elements are uniformly distributed in the 1T′-WS2 gel. This uniform dispersion effectively confines the heat generated by solar energy within the molecular framework, thereby reducing heat loss to the bulk and improving interfacial heating efficiency.

[0139] FTIR analysis ( Figure 12A Further confirmation by Raman spectroscopy and XPS characterization indicates that the WS2 nanosheets have been incorporated into the polyvinyl alcohol matrix. Figure 12B-12C This confirms that the 1T′ phase retains its structural integrity after being embedded in the hydrogel.

[0140] It is worth noting that efficient solar thermal evaporation largely depends on the full absorption of a broad solar spectrum. The solar absorption properties of each group of hydrogel samples were characterized using ultraviolet-visible-near-infrared (UV-Vis-NIR) spectroscopy. Figure 13A As shown, the hydrated 1T′-WS2 gel exhibits excellent light absorption in a wide wavelength range of 200-2000 nm. Compared with other control groups ( Figure 13B-13C Its reflectivity and transmittance both decreased significantly. Considering the non-uniformity of solar spectral energy distribution, the solar absorptivity (α), i.e., the ratio of absorbed energy to incident radiation energy, is used as the evaluation index. Compared with the conventional average absorptivity, α can more representatively measure the photothermal conversion performance of the material. The value of α is calculated based on the measured reflectance and transmittance spectra and according to the following formula (1): (1) Where I(λ), R(λ) and T(λ) represent the AM1.5G solar spectral irradiance, reflectance and transmittance as varying with wavelength, respectively.

[0141] The calculated α values ​​for each sample in the range of 200-2000 nm are summarized in Table 3.

[0142] Table 3 - Comparison of UV-Vis-NIR absorbance of pure gel, 2H-WS2 gel and 1T'-WS2 gel under wet and dry conditions.

[0143] The solar absorptivity of the hydrated 1T′-WS2 gel was approximately 0.98, significantly higher than that of the hydrated 2H-WS2 gel (approximately 0.76) and the pure gel (approximately 0.14). A similar trend was observed in the dry state, with solar absorptivity of 1T′-WS2, 2H-WS2, and the pure gel being approximately 0.97, 0.78, and 0.04, respectively. Figures 14A-14C The above results highlight that the 1T′-WS2 gel phase has significantly superior solar energy harvesting capabilities compared to the 2H phase and the pure gel, laying a solid foundation for its efficient solar-driven water evaporation.

[0144] Example 6 - Performance Evaluation and Desalination Test

[0145] To evaluate the solar-driven water evaporation performance of 1T′-TMD gels, including 1T′-WS2 gel, experiments were conducted under controlled environmental conditions: temperature 20 ± 2°C and relative humidity 65 ± 5%. A xenon lamp equipped with an AM1.5G filter was used to provide simulated sunlight. The spot size was controlled by an aperture to avoid illuminating areas outside the evaporator. The xenon lamp was preheated for at least 30 minutes until it reached a stable state before any measurements were taken. The solar flux was varied by adjusting the current and calibrated using a power meter to ensure that the actual light intensity was accurately maintained at 1 kWm. -2 .

[0146] The hydrogel was placed on polystyrene foam covered with lint-free paper to achieve thermal insulation and moisture transport. The photothermal behavior was evaluated by monitoring the temperature changes over time of the bulk water on and beneath the surface of each hydrogel under 1 day of sunlight irradiation. Figure 15 Within 10 minutes of illumination, the surface temperatures of both the 1T′-WS2 and 2H-WS2 gels showed a rapid upward trend. The steady-state temperature reached by the 1T′-WS2 gel was approximately 32.5°C, while that of the 2H-WS2 gel stabilized at around 28.8°C. Notably, the temperature of the bulk water beneath the 1T′-WS2 gel remained stable at 22-23°C, indicating that heat was effectively confined within the evaporation layer. Infrared thermal images captured at 0, 10, 30, and 60 minutes (…) Figure 16 Further confirmation indicates that the surface temperature of the 1T′-WS2 gel is higher than that of the 2H-WS2 gel and the pure gel, and that the heat energy is mainly retained at the evaporation interface rather than dissipated into the bulk water.

[0147] Furthermore, the lateral temperature of the hydrogel remains below the ambient temperature, indicating that heat flows into the system from the surrounding environment through lateral heat exchange. Therefore, during water evaporation, the energy input originates both from direct solar radiation to the gel surface and from ambient heat absorbed through the sides of the three-dimensional gel structure.

[0148] By tracking the liquid mass loss over time ( Figure 17 The water evaporation performance of three solar evaporators under one solar illumination condition was evaluated. Under one solar illumination condition, the 1T′-WS2 gel containing 0.26 wt% solute exhibited the highest evaporation rate, reaching approximately 3.6 kg m³. -2 h -1 Its performance is significantly better than that of 2H-WS2 gel (approximately 2.6 kg m³). -2 h -1 and pure PVA gel (approximately 1.4 kg m -2 h -1To accurately assess the system's energy budget, quantitative calculations were performed for reflection loss, convection loss, radiation loss, and conduction loss for each hydrogel sample (Table 4). Experimental data show that the 1T′-WS2 hydrogel effectively suppressed all heat losses, with its cumulative energy loss significantly lower than that of the 2H phase. Reflection loss and conduction loss were as low as 0.009 W·h and 0.001 W·h, respectively, demonstrating its excellent light-harvesting ability and thermal localization effect.

[0149] Table 4 - Calculation parameters for photothermal evaporation performance Symbol explanation: R: Evaporator radius; Q sol Total solar input power; A: Optical absorptivity; H: Evaporator height; A lat and T lat : Side surface area and side surface temperature; A surf and T surf Top surface area and surface temperature; T env Ambient temperature; m bulk : Bulk water mass; T ini and T end The initial and final temperatures of the bulk water phase.

[0150] Thermal conductivity characterization revealed that the 1T′-WS2 gel exhibited low thermal conductivity (0.539 W / m²). -1 K -1 , with pure polyvinyl alcohol gel (0.536 W m -1 K -1 Comparable to, but lower than, 2H-WS2 gel (0.605 W m). -1 K -1 This helps to suppress the dissipation of heat into the lower body water phase.

[0151] The photothermal evaporation efficiency ƞ of the hydrogel evaporator is determined by comprehensively considering the input solar energy and the main heat loss pathways: (2) Total solar energy input ( The calculation formula is as follows: (3) in, For the optical focusing magnification of the solar simulator, It is the nominal direct solar irradiance (1 kW m). -2 ), It is the top surface area of ​​the evaporator. It refers to the duration of irradiation.

[0152] Total heat loss ( The heat loss mainly originates from: (1) conductive heat loss from the evaporator to the bulk water; (2) radiative heat loss from the evaporator to the environment; and (3) convective heat loss from the evaporator to the environment; which can be described by the following formula: Solar energy loss due to reflection ( Estimate using the following formula: , where R is the solar reflectance of the evaporator.

[0153] The photothermal evaporation efficiencies (ƞ) of the pure gel, 2H-WS2 gel, and 1T′-WS2 gel were 16.5%, 68.0%, and 90.0%, respectively. Figure 18 The 1T′-WS2 gel exhibits energy utilization efficiency far exceeding that of the comparative samples, fully demonstrating its superior performance in solar energy capture and thermal energy conversion. This significant performance gain stems from the broad-spectrum absorption resulting from the abundant active sites in the 1T′ phase, and the highly efficient photothermal conversion process driven by its metallic properties. Notably, the 1T′-WS2 gel demonstrates a water evaporation rate superior to previously reported TMD-based evaporators with various phase structures. Figure 19 ).

[0154] To elucidate the underlying mechanism of enhanced evaporation performance, this embodiment first uses differential scanning calorimetry (DSC) to determine the enthalpy of vaporization of bulk water and hydrogel systems.

[0155] Bulk water exhibits a sharp endothermic peak with rapid decay characteristics. Figure 20 The obtained vaporization enthalpy was 2501 J g⁻¹, which is consistent with the theoretical value of 2450 J g⁻¹. -1 The results showed a high degree of agreement. In contrast, all hydrogels exhibited broadened endothermic peaks and gradual decay, indicating a fundamental difference in their evaporation kinetics compared to pure water. Among them, the 1T′-WS2 gel exhibited the lowest enthalpy of vaporization (1566 J g). -1 The energy required for evaporation to produce steam is significantly reduced. FTIR analysis revealed different water binding environments related to the phase. Compared to the 2H phase, the 1T′ phase exhibits a significant blue shift in its spectrum, accompanied by an increase in the proportion of weakly hydrogen-bonded species. This reflects a weakening of hydrogen bond strength and a decrease in the desorption energy barrier. Figures 21A-21B ).

[0156] In addition, this embodiment also recorded the Raman spectra of three types of hydrogels and interfacial water on bulk water. Figures 22A-22C Four characteristic peaks were identified through Gaussian function fitting: 3233 cm⁻¹ -13401 cm⁻¹ and 3514 cm⁻¹ correspond to the in-phase and out-of-phase vibrational modes of fully hydrogen-bonded free water molecules with four hydrogen bonds, respectively; while 3514 cm⁻¹ and 3630 cm⁻¹ correspond to the symmetric and asymmetric stretching vibrations of interfacial water molecules with fewer hydrogen bonds, respectively.

[0157] Raman OH stretching vibration belt (3000-3650 cm) -1 After deconvolution processing, four characteristic peaks belonging to different hydrogen bond states were obtained: the characteristic peaks at 3233 cm⁻¹ and 3401 cm⁻¹ correspond to free water (FW) with a complete hydrogen bond network; while the characteristic peaks at 3514 cm⁻¹ and 3630 cm⁻¹ correspond to interfacial water (IW) with fewer hydrogen bonds. By integrating the relative contribution of the area of ​​each characteristic peak, the component proportions of FW and IW in the system and the IW / FW molar ratio were quantitatively calculated. The results show that the 1T′-WS2 gel exhibits the highest IW proportion and the largest IW / FW ratio, confirming the presence of abundant weakly hydrogen-bonded water species within it, thus effectively optimizing the evaporation kinetics. As summarized in Table 5, the 1T′-WS2 gel exhibits the highest IW content (approximately 26.8%) and the largest IW / FW ratio (0.37:1), significantly superior to bulk water (21.2%, 0.27:1), 2H-WS2 gel (22.0%, 0.28:1), and pure polyvinyl alcohol gel (11.6%, 0.13:1). Given that the evaporation rate of IW is significantly faster than that of fully hydrogen-bonded water molecules, this enrichment of interfacial water provides a molecular-level explanation for the lower vaporization enthalpy observed in DSC tests. In summary, through multidimensional characterization using DSC, FTIR, and Raman, this invention establishes a complete regulatory mechanism: the half-metallic 1T′ phase can effectively weaken the hydrogen bonding interactions between water molecules, thereby inducing the generation of abundant interfacial water components, significantly reducing the vaporization enthalpy of water evaporation from a thermodynamic perspective. This phase-dependent regulation of the interfacial water state provides a molecular-level theoretical basis for the superior solar-driven evaporation performance of the 1T′-WS2 gel.

[0158] Table 5 - Raman peak deconvolution analysis of interfacial water

[0159] In the seawater desalination experiment, sodium chloride was directly dissolved in deionized water to prepare simulated seawater of different concentrations (3.5%, 10%, and 20% wt%). In addition, a solar-powered seawater desalination experiment was conducted using real seawater samples collected from the Saigon sea area. Thermal images were captured using an infrared thermal imager. Real-time temperature distribution and bulk water temperature were measured using thermocouples and recorded by a data acquisition system. Mass changes during steam generation were recorded every 10 minutes using an electronic balance (accuracy 0.001 g). The salt ion concentration in the resulting distilled water was analyzed using ion chromatography and inductively coupled plasma mass spectrometry.

[0160] The long-term stability of the system was evaluated by conducting an evaporation experiment for 100 hours in an open environment using 3.5% saline solution. Under one solar irradiance, the hydrogel maintained a mass of 3.47 ± 0.27 kg m³. -2 h -1 Average evaporation rate (e.g.) Figure 23 (As shown). After 10 hours of continuous operation, only trace amounts of salt deposition were observed, and the deposited salt disappeared immediately after the light was turned off. This reveals that the system has an inherent self-cleaning ability, enabling continuous evaporation during the day and performance recovery at night.

[0161] Raman spectroscopy and XPS characterization after testing are as follows: Figures 24A-24B As shown in the figure, the 1T′ phase remained intact after 100 hours of operation, demonstrating its excellent long-term structural stability. In addition to chemical and phase stability, this hydrogel also exhibits outstanding mechanical robustness. The hydrogel can withstand compressive stresses up to 350 kPa under near-complete deformation conditions without fracturing (e.g., Figures 25A-25B (As shown). In cyclic compression tests at 50% strain, the maximum stress decrease was less than 10% after 100 cycles, demonstrating excellent fatigue resistance. This superior mechanical robustness, combined with its efficient water evaporation performance, salt resistance, and long-term phase stability, highlights the enormous application potential of 1T′-WS2 gel as a durable and scalable platform in practical solar desalination.

[0162] Example 7 - Verification of the universality of various 1T′-TMD and surface modifications

[0163] To evaluate the universality of the technical advantages of the phase engineering strategy, this example synthesized several 1T′-TMD crystals other than WS2, including 1T′-MoS2, 1T′-MoSe2, and 1T′-WSe2. Subsequently, these crystals were fabricated into nanosheets using the aforementioned salt-assisted method and ultrasonic exfoliation. Raman spectroscopy and photographic characterization confirmed that all tested transition metal varieties exhibited high phase purity and uniform dispersion. Figures 26A-26C ).

[0164] g-C3N4 was prepared by direct heating of urea (without any additives). In a typical synthesis, 8 g of melamine was placed in a covered crucible and then heated in a muffle furnace at 5 °C for min. -1 The temperature was increased to 550 °C and held for 2 hours. The synthesized bulk phase g-C3N4 was ground into powder, placed in an uncovered crucible, and heated in a muffle furnace at 5 °C for 2 minutes. -1 The temperature was increased to 500 °C and held for 5 hours to obtain g-C3N4 nanosheets. Subsequently, 0.1 g of g-C3N4 nanosheets were mixed with 1 mL of 1T′-WS2 nanosheet suspension or 2H-WS2 nanosheets under stirring. The synthesis of 1T′-WS2 / g-C3N4 gel and 2H-WS2 / g-C3N4 gel was performed using the same process as for 1T′-WS2 gel, except that the 1T′-WS2 suspension was replaced with the 1T′-WS2 / g-C3N4 composite material and the 2H-WS2 / g-C3N4 composite material, respectively.

[0165] Photographic images showed that each sample possessed vivid color and uniform dispersion. Meanwhile, Raman analysis confirmed that they all exhibited extremely high phase purity. Using the same process, these nanosheets were introduced into the hydrogel matrix. UV-Vis-NIR spectroscopy revealed that, compared to the corresponding 2H phase hydrogel, all 1T' phase-based hydrogels showed significantly enhanced light absorption in the 200-2000 nm wavelength range. Figure 27A Accordingly, photothermal evaporation test ( Figure 27B-27C This demonstrates that hydrogels based on the 1T' phase exhibit a consistent and higher evaporation rate.

[0166] In another embodiment, the photothermal properties of 1T′-TMD nanosheets are further enhanced by surface modification with noble metal nanoparticles, such as silver nanoparticles. Structural analysis shows that silver nanoparticles are uniformly decorated on the surface of the 1T′-WS2 nanosheets, with an average particle size distribution between 5 nm and 20 nm. This surface decoration induces a strong localized surface plasmon resonance (LSPR) effect, effectively extending the absorption of sunlight across the entire wavelength range and promoting the redistribution of hot carriers.

[0167] Example 8 - Outdoor Solar Evaporation Performance Test

[0168] To assess the feasibility of continuous water production under real-world conditions, a self-made solar evaporation device was used. Figures 28A-28B Outdoor experiments were conducted.

[0169] The water production performance of large-scale samples was verified on an outdoor rooftop platform using a 1T′-WS2 gel evaporator (150 mm × 100 mm × 10 mm). A self-made double-sloping solar distillation apparatus was used for steam condensation and water collection. Seawater from Victoria Harbour was pre-filtered through a 0.22-micron membrane before being introduced into the closed reactor for distillation. The system utilizes natural sunlight as its energy source, and real-time solar flux and temperature were recorded hourly using a power meter and a thermometer. The concentration of dye molecules in the distilled water was analyzed using a UV-Vis spectrophotometer.

[0170] To test the performance of simultaneous water evaporation and volatile organic compound (VOC) degradation, simulated feed water containing phenol was introduced into a sealed quartz reactor, and a distillation process was carried out under solar illumination. After adsorption-desorption equilibrium was reached under light-shielded conditions for 1 hour, the degradation efficiency of all samples was determined. The phenol concentration in the feed water and collected solution was determined using high-performance liquid chromatography (HPLC) with an Agilent ZORBAX EclipsePlus C18 column (4.6 × 150 mm, 3 μm). Electrochemical impedance spectroscopy (EIS) was performed on a CHI 660E electrochemical workstation using a standard three-electrode system. Photocurrent response measurements were performed in a standard three-electrode electrochemical cell, including a working electrode, a platinum plate as a counter electrode, and a saturated silver / silver chloride electrode as a reference electrode. A 0.2 M Na₂SO₄ aqueous solution (pH = 6.8) was used as the electrolyte. The working electrode for photocurrent response testing was prepared as follows: 2 mg of catalyst was dispersed in a mixed solution of 990 μL ethanol and 10 μL Nafion D-520 dispersion to produce a homogeneous slurry. Subsequently, 200 μL of the slurry was transferred and coated onto an ITO glass plate (1 cm × 1 cm) and then dried at room temperature.

[0171] like Figure 29 As shown, the experiment was conducted under natural sunlight from 09:00 to 18:00, with an average solar heat flux of approximately 0.59 kW m³. -2 1T′-WS2 gel achieves approximately 0.682 kg m⁻² h. -1 The average hourly water collection rate resulted in a cumulative water production of approximately 6.14 L / m³ over 9 hours. -2 No salt precipitation was observed. A large amount of droplet accumulation was observed at the top of the device, and the system reached thermal steady state with a peak surface temperature of approximately 52 °C. Figure 30 This demonstrates the achievement of effective thermal localization. The significant temperature difference between the gel surface and the surrounding environment further confirms the effectiveness of local heating, which is crucial for maintaining high evaporation efficiency.

[0172] Water quality analysis shows that the main cations in the desalinated water are Na+. + Mg 2+ Ca 2+ and K + ) and anions (Cl − SO4 2− , and Br − The concentration of ) was reduced by about three orders of magnitude relative to the influent. Figure 31 Specifically, the sodium ion concentration in the treated water was measured to be 6.63 mg / L. -1 It is far below the drinking water standard set by the World Health Organization (200-250 mg / L). -1 This confirms the system's effectiveness in producing high-quality drinking water.

[0173] Example 9 - Multifunctional Wastewater Treatment and Purification Performance Test

[0174] To evaluate the versatility of phase-engineered 1T′-WS2 gel beyond seawater desalination, this case study investigates its performance in treating various industrial wastewater pollutants. A solar evaporator based on 1T′-WS2 gel was used to treat water samples containing heavy metal ions and industrial dye contamination.

[0175] like Figure 32 As shown, this system can significantly reduce the concentration of various heavy metal ions, including chromium, copper, nickel, zinc, and gallium ions. After a solar-driven purification process, the final concentrations of these ions are all reduced to below 0.1 ppm, with a removal rate exceeding 99.98%. These results confirm the extremely high efficiency of 1T′-WS2 gel in producing safe drinking water from heavily polluted water sources.

[0176] In addition to heavy metal remediation, this case study also evaluated the removal capacity of 1T′-WS2 gel for organic dye contaminants, particularly its purification effect on methyl orange and methylene blue. UV-Vis absorption spectroscopy analysis confirmed ( Figure 33 The system completely removes these industrial dyes, producing clear and colorless pure water.

[0177] Example 10 - Performance Test of Synergistic Photothermal Evaporation and Photocatalytic VOC Degradation

[0178] To extend the functionality of the 1T′-TMD platform beyond seawater desalination, a multifunctional composite hydrogel was prepared by coupling semi-metallic 1T′-WS2 nanosheets with graphitic carbon nitride (g-C3N4) using a self-assembly strategy. This hybrid system aims to investigate the coupling performance between solar-driven water evaporation and VOC photodegradation.

[0179] HRTEM and EDS elemental distribution map ( Figure 34AThis confirms the homogeneous integration of 1T′-WS2 and g-C3N4, while XPS images further reveal the electronic interactions between the interfaces. In the W4f energy spectrum of the composite material ( Figure 34B ), belongs to W4f 5 / 2 and W4f 7 / 2 The characteristic peaks are located at 33.5 eV and 31.3 eV, respectively, shifted by approximately 0.5 eV towards lower binding energies compared to pure 1T′-WS2. In the N1s spectrum, compared to pure g-C3N4, the characteristic peaks belonging to CN=C, N-(C)3, and CNH are all shifted towards higher binding energies. These shifts indicate that electrons are transferred from g-C3N4 to 1T′-WS2, confirming the formation of a built-in electric field pointing from the semiconductor phase to the half-metal phase.

[0180] Complementary FTIR and Raman spectra ( Figures 35A-35B The successful formation of the composite material was verified, and it was shown that the phase structures of both components remained intact. For comparison, a 2H-WS2 / g-C3N4 composite material was also prepared. The carrier separation and transport characteristics of the composite material were explored through photoelectrochemical characterization. The photocurrent density of the 1T'-WS2 / g-C3N4 system was 6.7 μA cm⁻¹. -2 The value is much higher than that of 2H-WS2 / g-C3N4 (0.8 μA cm⁻¹). -2 ) and pure g-C3N4 (0.02 μA cm) -2 This indicates that 1T′-WS2 significantly enhances the generation and transport of photogenerated electrons. Figure 35C ).

[0181] In addition, EIS measurements ( Figure 35D This shows a decrease in charge transfer resistance and an increase in carrier mobility, while the photoluminescence spectrum ( Figure 35E The emission intensity was significantly suppressed, indicating that electron-hole recombination was effectively inhibited. The improved charge transport performance is mainly attributed to the high conductivity, which effectively promotes rapid electron transport and suppresses electron-hole recombination.

[0182] Given the enhanced interfacial charge kinetics, this was subsequently achieved in a custom-designed closed quartz reactor ( Figure 35F The removal performance of 1T′-WS2 / g-C3N4 gel for VOCs was evaluated using phenol as a model pollutant. After one hour of illumination, the degradation efficiency of 1T′-WS2 / g-C3N4 gel reached 98.1% ( Figure 35G The phenol content was higher than 2H-WS2 / g-C3N4 (approximately 83%), approaching complete phenol removal. More importantly, the mixed hydrogel maintained approximately 3.5 kg m³ under 1°C sunlight irradiation. -2 h -1 Its high evaporation rate is comparable to that of pure 1T′-WS2 hydrogel. Figure 35HThis demonstrates that integration with g-C3N4 does not impair evaporation performance. In summary, these results indicate that coupling semi-metallic 1T′-WS2 nanosheets with semiconductor photocatalysts can achieve a synergistic effect of efficient photothermal evaporation and photocatalytic VOC degradation, thus establishing a general strategy for constructing multifunctional solar energy purification systems.

[0183] Example 11 - Comparative Analysis of the Performance of 1T′-TMD and 2H Phase TMD

[0184] To demonstrate the superior technical performance of the half-metal 1T′ phase compared to the conventional semiconductor 2H phase, this example presents a comprehensive comparative analysis of aspects such as light absorption, water activation, and charge carrier dynamics.

[0185] refer to Figures 36A-36C Compared to other hydrogels, this hydrogel exhibits the lowest reflectance and transmittance across the entire wavelength range. The solar absorptivity of the 1T′-WS2 gel is approximately 0.98, that of the 2H-WS2 gel is approximately 0.76, and that of the pure gel is only 0.14.

[0186] like Figures 37A-37C As shown, this example also tested the solar absorption, transmission, and reflection spectra of three hydrogels in the dry state. In the dry state, the average solar absorption rate of 1T′-WS2 gel was approximately 0.97, that of 2H-WS2 gel was approximately 0.78, and that of the pure gel was only 0.04.

[0187] Furthermore, this invention demonstrates versatility in applications, achieving efficient photodegradation of various water pollutants, including volatile organic compounds, dyes, antibiotics, and pesticides, by integrating 1T′-TMD with semiconductor catalysts (such as g-C3N4, TiO2, and ZnO). The semi-metallic properties and superior electron transport capabilities of 1T′-TMD effectively reduce electron-hole recombination rates, thereby enhancing photodegradation efficiency.

[0188] This combination enhances the photocatalytic ability of the materials, enabling the effective degradation of a variety of water pollutants. The dual function of water evaporation and pollutant degradation makes these materials an advanced solution for next-generation water treatment systems.

[0189] In summary, this invention successfully establishes phase-engineered 1T′-TMD as an inherently efficient and stable platform for advanced solar-driven water purification systems. This invention utilizes the semi-metallic properties of the 1T′ phase to provide broad-spectrum solar energy capture capabilities and a non-radiative relaxation path. The long-lived carrier absorption and plasmon bleaching observed in ultrafast spectral analysis strongly confirm these physical properties. These electronic characteristics offer a decisive advantage over the rapidly decaying exciton response of conventional 2H phase materials, ensuring higher photothermal conversion efficiency and enhanced stability under environmental conditions.

[0190] Integrating 1T′-TMD nanosheets into a porous hydrogel matrix yields significant thermodynamic advantages, particularly by effectively reducing the activation enthalpy of water molecules through the enrichment of intermediate water species. This synergistic configuration achieves extremely high evaporation rates and photo-steam conversion efficiencies, far exceeding those of existing TMD-based evaporators. Furthermore, the interconnected structural design provides robust salt tolerance and self-cleaning capabilities, enabling continuous and stable freshwater production even under high salinity conditions where scaling typically occurs in conventional systems.

[0191] In addition to desalination, this invention also constructs a multifunctional hybrid system by coupling 1T′-TMD with a semiconductor catalyst. The high electron transport capability of the 1T′ phase suppresses electron-hole recombination, thereby significantly improving the photocatalytic degradation efficiency of organic pollutants such as phenol. This integrated approach enables the simultaneous generation of pure water and in-situ removal of pollutants without affecting their performance. Therefore, the 1T′-TMD gel can serve as a scalable, durable, and cost-effective platform for next-generation environmental remediation and sustainable water resource management.

[0192] The foregoing description of the invention has been provided for purposes of illustration and description. The foregoing description is not intended to be exhaustive or to limit the invention to the precise forms disclosed. Many modifications and variations will be apparent to those skilled in the art.

[0193] The embodiments have been selected and described in order to best explain the principles of the invention and its practical application, thereby enabling others skilled in the art to understand the invention with respect to the various embodiments and with various modifications suitable for the intended particular application.

[0194] References: All publicly available information in the following references is incorporated into this paper through citation. 1. Mechanically interlocked 1T / 2H phase MoS2 nanosheets for solar thermal-driven water purification. Nano Energy, 2018, 53, 949-957. 2. Molybdenum disulfide stabilized metal 1T phase engineering for enhancing solar vapor generation. *Solar Materials and Solar Cells* (Sol. Energ. Mat. Sol. C.), 2020, 204, 110227. 3. U.S. Patent Application Publication No. 2022 / 0348476A1 4. Chinese Patent No. CN112707391B 5. Chinese Patent No. CN115746383A 6. Synthesis of a water- and air-stable, superconducting 1T' phase WS2 monolayer ink. Science Advances, 9, eadd6167 (2023).

Claims

1. A photothermal gel for solar-driven water evaporation and pollutant removal, characterized in that, The photothermal gel comprises: A polymer matrix comprising an interconnected porous framework; and Semi-metallic 1T' phase transition metal chalcogenide (1T'-TMD) nanosheets are distributed within and anchored to the interconnected porous framework. The concentration of the 1T'-TMD nanosheets ranges from 0.5 wt% to 8.0 wt% based on the total weight of the hydrogel.

2. The temperature-sensitive silicone rubber-based composite material according to claim 1, wherein the 1T'-TMD nanosheets comprise a transition metal M and a chalcogenide element X, represented by the chemical formula MX2, wherein M is selected from the group consisting of tungsten (W) and molybdenum (Mo), and X is selected from the group consisting of sulfur (S) and selenium (Se).

3. The temperature-sensitive silicone rubber-based composite material according to claim 2, wherein the 1T'-TMD nanosheets comprise 1T' phase tungsten disulfide (1T'-WS2).

4. The temperature-sensitive silicone rubber-based composite material according to claim 1, wherein the average thickness of the 1T'-TMD nanosheets ranges from 0.7 nm to 2.1 nm.

5. The temperature-sensitive silicone rubber-based composite material according to claim 1, wherein the polymer matrix is ​​selected from the group consisting of polyacrylic acid, polyvinyl alcohol, polyethylene glycol, sodium polyacrylate, polyacrylamide, polyethyleneimine, polystyrene sulfonic acid, and sodium polystyrene sulfonate.

6. The temperature-sensitive silicone rubber-based composite material according to claim 1, wherein the photothermal hydrogel, in a dry state, exhibits a solar absorption rate of at least 0.9 in the wavelength range of 200 nm to 2000 nm.

7. The temperature-sensitive silicone rubber-based composite material according to claim 1, wherein the photothermal hydrogel further comprises noble metal nanoparticles modified on the surface of the 1T'-TMD nanosheets, and further comprises at least one semiconductor catalyst coupled to the 1T'-TMD nanosheets.

8. The temperature-sensitive silicone rubber-based composite material according to claim 7, wherein the noble metal nanoparticles are silver nanoparticles with an average particle size distribution between 5 nm and 20 nm.

9. A photocatalytic-photothermal composite system for solar-driven water evaporation and photodegradation of volatile organic compounds, characterized in that, The photocatalytic-photothermal composite system includes: A hydrogel matrix comprising half-metallic 1T'-TMD nanosheets integrated into a cross-linked polymer network; and At least one semiconductor catalyst is in direct interfacial contact with the 1T'-TMD nanosheets to form a semiconductor / 1T'-TMD interfacial heterojunction. The interface heterojunction promotes charge carrier separation between the semiconductor catalyst and the 1T'-TMD nanosheets, and the half-metallic 1T'-TMD nanosheets act as an electron transport medium.

10. The photocatalytic-photothermal composite system according to claim 9, wherein the at least one semiconductor catalyst is selected from the group consisting of graphitic carbon nitride, titanium dioxide, zinc oxide, iron oxide, bismuth halogen oxide and cadmium sulfide.

11. The photocatalytic-photothermal composite system according to claim 9, wherein the mass ratio of the at least one semiconductor catalyst to the 1T'-TMD nanosheet ranges from 5:1 to 50:

1.

12. The photocatalytic-photothermal composite system according to claim 9, wherein the volatile organic compound includes phenol, aniline, formaldehyde, benzene or toluene.

13. The photocatalytic-photothermal composite system according to claim 9, wherein the photocatalytic degradation efficiency of phenol by the system is in the range of 80% to 99% after irradiation for 60 minutes under a solar irradiance of 1.

14. The photocatalytic-photothermal composite system according to claim 9, wherein the system further comprises a water supply component configured to deliver source water to the hydrogel matrix via capillary action, wherein the hydrogel matrix is ​​located at the gas-water interface.

15. A method for preparing hydrogels based on 1T'-TMD, characterized in that, The method includes: A mixture containing a 2H phase TMD precursor, a potassium-based salt auxiliary agent, and a sulfide source was heated in a reducing atmosphere at a temperature of 700°C to 900°C to synthesize a 1T' phase crystal. The 1T' phase crystal was exfoliated to obtain a 1T'-TMD nanosheet suspension; The 1T'-TMD nanosheets were dispersed in a hydrophilic polymer solution containing a crosslinking agent, and a pregel mixture was formed by uniform mixing; and The mixture was subjected to instantaneous freezing treatment, thereby constructing an interconnected submicron porous structure while maintaining the half-metallic 1T' phase. The exfoliation rate of the 1T'-TMD nanosheets is at least 80% relative to the total mass of the exfoliated nanosheets obtained from the 1T' phase crystal.

16. The method of claim 15, wherein the stripping step is performed by ultrasonic treatment in an acidic solution containing H2SO4 at a concentration of 0.1 M to 1.0 M.

17. The method according to claim 15, wherein the potassium-based salt additive is selected from the group consisting of potassium oxalate, potassium oxalate monohydrate, potassium carbonate and potassium bicarbonate, the sulfur source is selected from the group consisting of sulfur (S) powder and selenium (Se) powder, and the 2H phase TMD precursor is selected from the group consisting of WS2 powder, MoS2 powder, WSe2 powder and MoSe2 powder.

18. The method according to claim 15, wherein the salt additive comprises potassium oxalate monohydrate, and the mass ratio of the 2H phase TMD precursor, the salt additive, and the sulfide source ranges from 1:0.5:1 to 1:1.5:

2.

19. The method of claim 15, wherein the hydrophilic polymer solution comprises polyvinyl alcohol in the concentration range of 100 mg / mL to 400 mg / mL.

20. The method of claim 15, wherein the method uses glutaraldehyde and an acid catalyst to perform crosslinking, wherein the concentration of the acid catalyst is maintained between 0.02 M and 0.1 M.

Citation Information

Patent Citations

  • A self-supplying photothermal evaporation device based on composite hydrogel

    CN112707391B

  • Composite membrane material, preparation method thereof and solar evaporator

    CN115746383A

  • Molybdenum sulfide powder and method for producing same, heavy-metal adsorbent, photothermal conversion material, distillation method, oxygen reduction catalyst, and catalyst ink

    US20220348476A1